Primary Vaginal Stones in Pediatric Patients: A Review of Literature - Chamma, Linda; Ballout, Ibrahim (International Journal of Clinical Research, 2025)
Introduction: Calculi, or stones are hard deposits that can precipitate in various anatomical regions. Colpolithiasis or vaginal stones are seldom seen in the clinical practice making the diagnosis and management challenging. Based on their pathophysiology, they can be classified into primary and secondary stones. It is noteworthy that many of the cases described in the literature belong to the pediatric category. Therefore, a special focus on pediatric cases is warranted in this review. We will be tackling the pathophysiology of vaginal stones in pediatric patients and focus on the adaptation of minimal invasive procedures in the management. Methods: A systematic review was conducted using PubMed, Scopus, and Web of Science databases up to January 2025. Data on demographics, causes, clinical features, diagnostics, and treatments were extracted and synthesized. Case reports and case series were assessed using the CARE guidelines to ensure relevance and quality. This review relied on publicly available data and did not require ethical approval. Discussion: In opposition to secondary stones primary stones crystallize in the absence of a nidus. In fact, urine stagnation is the cornerstone for primary stone formation. Factors contributing to urine stasis in the vagina include prolonged immobilization and urogenital anatomical abnormalities. Prolonged immobilization was linked to patients with neurological disorders whereas anatomical abnormalities were predominantly described as vaginal outlet obstruction and urethrovaginal fistula. Transvaginal extraction of stones has been mainly adapted for treatment in pediatric patients and it is preferred over the trans abdominal approach as it is less invasive and carries fewer risks. Conclusion: Primary vaginal stones are seldom described. They are multifactorial as multiple factors play a role in their pathogenesis such as urinary stasis, urinary incontinence, and infection. They are often seen among the pediatric population with neurological disorders or with urogenital anomalies either congenital or acquired. Their management is still not well-established, but there is a tendency toward safer endourological methods more suitable for pediatrics and patients with specific needs.